Potential food additive of Boswellia carterii essential oil encapsulated within gum Arabic: a particle size distribution and zeta potential analysis - Barre, Mohamed Soleiman (Rynnye Lyan Resources, 2020)
Boswellia carterii (BC) Burseraceae family essential oil (EO) were extracted by hydrodistillation process. Gum Arabic (GA) Acacia senegal polymer particles containing a BCEO were prepared by spray drying technique. The mean particle size and its distribution, as well as the zeta-potential of the microcapsules, were analyzed and found Z-Average 382±203nm, PDI 0.77±0.3, ZP-25±2.73mV, respectively. Product encapsulation efficiency (EE %) was found at 75±0.8%. The surface morphology of the particles was obtained by scanning electron microscope (SEM). Furthermore, particles moisture content was analyzed by the oven drying method. The efficiency of encapsulation (EE %) was estimated by specifying the content of essential oil in the product. Gas chromatography (GC) coupled with time-of-flight mass spectrometry (TOFMS) analysis of EO has been performed to determine the chemical compounds and their prevalence concentrations respectively. The composition of initial essential oil (added in the emulsion) and the encapsulated essential oil (extracted from spray dried powder) were analyzed and compared. The outcome of the research encourages the high potentiality and usefulness of the product in the food industries sector as a food additive agent, moreover, it suggests for further research to unravel potential implementation of BCEO microcapsules in the food production chain